Advances and perspectives in carrier-free nanodrugs for cancer chemo-monotherapy and combination therapy. (January 2021) - Huang, Li; Zhao, Shaojing; Fang, Fang; Xu, Ting; Lan, Minhuan; Zhang, Jinfeng
Abstract: Nanocarrier-based drug delivery systems hold impressive promise for biomedical application because of their excellent water dispersibility, prolonged blood circulation time, increased drug accumulation in tumors, and potential in combination therapeutics. However, most nanocarriers suffer from low drug-loading efficiency, poor therapeutic effectiveness, potential systematic toxicity, and unstable metabolism. As an alternative, carrier-free nanodrugs, completely formulated with one or more drugs, have attracted increasing attention in cancer therapy due to their advantage of improved pharmacodynamics/pharmacokinetics, reduced toxicity, and high drug-loading. In recent years, carrier-free nanodrugs have contributed to progress in a variety of therapeutic modalities. In this review, different common strategies for carrier-free nanodrugs preparation are first summarized, mainly including nanoprecipitation, template-assisted nanoprecipitation, thin-film hydration, spray-drying technique, supercritical fluid (SCF) technique, and wet media milling. Then we describe the recently reported carrier-free nanodrugs for cancer chemo-monotherapy or combination therapy. The advantages of anti-cancer drugs combined with other chemotherapeutic, photosensitizers, photothermal, immunotherapeutic or gene drugs have been demonstrated. Finally, a future perspective is introduced to highlight the existing challenges and possible solutions toward clinical application of currently developed carrier-free nanodrugs, which may be instructive to the design of effective carrier-free regimens in the future.